PENGARUH HARGA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN DAN DAMPAKNYA PADA LOYALITAS NASABAH ADIRA FINANCE DI KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Nardiman Nardiman; Yasri Hasim (Program Studi Magister Manajemen, 2015)
This study aims to find: 1) the effect of price on customer satisfaction, 2) the effect of promotions on customer satisfaction, 3) the impact of service quality on customer satisfaction, 4) the effect of price on customer loyalty, 5) the effect on customer loyalty promotion, 6) the effect of service quality on customer loyalty, 7) the effect of customer satisfaction on customer loyalty Adira Finance in Sub Kinali West Pasaman. Type of research is ex post-facto, the study population is customer Kinali Adira Finance in District 890. Proportional sampling technique is simple random sampling. Samples totaling 110 people. Primary data was collected through a questionnaire using a Likert scale models that have been tested validity and reliability. The data analysis technique used is the Path Analysis (Path Analysis). The results of the study are: 1) There is a positive and significant impact on customer satisfaction rates, 2) There is a positive and significant impact on customer satisfaction campaign, 3) There is a positive and significant impact of service quality on customer satisfaction, 4) There is a positive and significant impact on the price customer loyalty, 5) there is no significant influence on customer loyalty promotion, 6) there is a positive and significant impact of service quality on customer loyalty, 7) there is a positive and significant impact on customer loyalty customer satisfaction Adira Finance in Sub Kinali West Pasaman. In terms of direct and indirect influence of price, promotion, quality of service and satisfaction to customer loyalty Adira Finance in Sub Kinali West Pasaman amounted to 36.66%, found that customer satisfaction had the greatest influence of 18.75%. This suggests that an understanding of the direct satisfaction has a major role to the emergence of customer loyalty in the District of Adira Finance Kinali West Pasaman. Keywords : Price, Promotion, Quality Service, Satisfaction, Loyalty